Peran Kepolisian dalam Pengendalian terhadap Penyampaian Pendapat di Muka Umum di Kota Medan - Supardi Sitinjak; Muhammad Ridwan Lubis (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
Terrorism is a serious threat to the security and unity of the Indonesian nation. Events such as the suicide bombing at the Medan Police Headquarters in 2019 show that acts of terror are increasingly complex and require swift and appropriate handling. For this reason, the government passed Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism as a legal basis that strengthens the authority of the apparatus, including the Gegana Detachment of the Indonesian National Police Mobile Brigade Corps (Brimob), in carrying out counter-terrorism operations. This study aims to determine and analyze how the implementation of Law No. 5 of 2018 is carried out by the Gegana Detachment in the North Sumatra Regional Police area, identify obstacles faced in operations, and formulate strategies to increase the effectiveness of the implementation of the law. The results of the study show that the implementation of this law has been implemented through preventive, preemptive, and repressive approaches, such as sterilization of places of worship, social activities "Love Sunday", security patrols, and anti-terror training simulations. However, implementation in the field still faces various obstacles, including limited modern equipment, lack of cross-agency coordination, and low public participation. Therefore, personnel capacity building, infrastructure modernization, and strengthening inter-agency synergy are needed to achieve more effective counterterrorism efforts in North Sumatra.